Electronic Transport Properties in GaAs/AlGaAs and InSe/InP Finite Superlattices under the Effect of a Non-Resonant Intense Laser Field and Considering Geometric Modifications (2022)
ABSTRACT: In this work, a finite periodic superlattice is studied, analyzing the probability of electronic transmission for two types of semiconductor heterostructures, GaAs/AlGaAs and InSe/InP. The changes in the maxima of the quasistationary states for both materials are discussed, making variations in the number of periods of the superlattice and its shape by means of geometric parameters. The effect of a non-resonant intense laser field has been included in the system to analyze the changes in the electronic transport properties by means of the Landauer formalism. It is found that the highest tunneling current is given for the GaAs-based compared to the InSe-based system and that the intense laser field improves the current–voltage characteristics generating higher current peaks, maintaining a negative differential resistance (NDR) effect, both with and without laser field for both materials and this fact allows to tune the magnitude of the current peak with the external field and therefore extend the range of operation for multiple applications. Finally, the power of the system is discussed for different bias voltages as a function of the chemical potential.